Plant production possibilities on a heavy metal contaminated soil with the purpose of biorefinery - Dergez, Ágnes; Blaskó, Lajos; Bordás, Diána; Zsigrai, György; Kiss, István; szabó, Sándor (Acta Agraria Debreceniensis, 2010)
Significant part of not cultivated area of Hungary is not suitable for agricultural utilization because of industrial pollution. Technologies of biorefinery make reutilization of contaminated areas possible. Biomass of plants produced on polluted soils can be raw material of valuable products. Applicability of biorefinery was tested on a heavy metal polluted soil, where the contamination originated from previous mining activity. Complete biomass utilization was aimed to obtain cosmetic ingredients, pharmaceutical agents, and precursors. During our research work 88 plant species and varieties were produced and tested for potential utilizable components. Levels of possible contaminants in these plants were monitored, and amounts of carbohydrates, protein, organic acid and cellulose were determined as well. Different plant extracts were tested as potential sources of biologically effective components or as raw materials for lactic acid fermentation. Our results show that biorefinery is a real possibility for utilization of polluted areas. Numerous plants could be cultivated on contaminated areas without increased levels of contaminants in their tissues, thus they can be sources of valuable compounds.